Temporal encephalocele: a novel indication for magnetic resonance‐guided laser interstitial thermal therapy for medically intractable epilepsy. Issue 3 (17th July 2019) - Ranjan, Manish; Wilfong, Angus W.; Borewinkle, Varina; Jarrar, Randa; Adelson, P. David
ABSTRACT: Temporal encephalocele (TE) is a rare but surgically treatable/curable cause of temporal lobe epilepsy (TLE). The surgical intervention varies from local disconnection to extensive anterior temporal lobectomy and amygdalohippocampectomy (ATL/AH). Magnetic resonance‐guided laser interstitial thermal therapy (MRgLITT) has evolved as a minimally invasive alternative for intractable epilepsy with good results, however, application of MRgLITT for intractable pediatric epilepsy secondary to TE has not been reported. We present a detailed technical report and clinical experience of MRgLITT in two adolescent children with medically intractable TLE secondary to TE. Pre‐surgical evaluation revealed anterior inferior TE with concordant clinico‐electrophysiological data. Both the patients underwent MRgLITT after review with the institutional multidisciplinary epilepsy team and discussion with the patient and the family. Both the patients were discharged on post‐operative day one and have been seizure‐free since the procedure at the last follow‐up visit at 18 months and 6 months, respectively. The present series demonstrates first‐ever clinical and technical experience of MRgLITT for TE with intractable pediatric epilepsy. The excellent post‐operative seizure outcome and favorable postoperative course support MRgLITT as the first line of surgical intervention for TE with intractable TLE and broadens the application of MRgLITT.